How do Catalan Students Narrate the History of Catalonia When They Finish Primary Education? - Sant, Edda; González-Monfort, Neus; Santisteban Fernández, Antoni; Pagès Blanch, Joan; Oller Freixa, Montserrat (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2015)
In this article we analyze how a group of Catalan students (aged 11-13, N = 245) narrate the history of Catalonia and we compare their narratives with the official Catalan narrative. From an interpretative approach, we collect data by requiring the students to write down what they remember about the history of Catalonia. The research is conducted by means of narrative analysis and normative content analysis. Our results suggest that most students’ narratives are similar to the official narrative in terms of the main characters and events selected and follow the patriotic national narrative by highlighting the relevance of Catalan national symbols. We discuss the implications of this patriotic national narrative in Catalonia and elsewhere, and we propose replacing patriotic national narratives with humanistic world history narratives.